The Potential Intravenous Drug Incompatibilities in PICU (Pediatric Intensive Care Unit) Patients at Dr. Moewardi Surakarta Hospital in 2024 - Sarti Teresia Dasmasela (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2026)
Drug incompatibility is a physical or chemical reaction between drug products that occurs outside the body and is characterized by precipitation, discoloration, gaseous products, and decreased drug effectiveness. Intravenous drug incompatibilities that occur in pediatric patients are at high risk of causing medication errors. Pediatric patients who are more at risk of drug incompatibility are patients admitted to the Pediatric Intensive Care Unit (PICU) because they receive more drugs intravenously. Therefore, this study was conducted to determine the potential for intravenous drug incompatibility in PICU patients at Dr. Moewardi Surakarta Hospital in 2024. This study is a descriptive observational non-experimental study and retrospective data collection at Dr. Moewardi Surakarta Hospital. The data taken were medical records of PICU patients who met the inclusion criteria of pediatric patients aged ≥28 days to 18 years, admitted to the PICU for at least 24 hours, and received intravenous drugs at least 2 drugs. The identification of potential incompatibility of intravenous drugs in PICU patients was then reviewed based on the Handbook of Injectable Drugs Information 2021 edition. The results showed that the compatibility of intravenous drugs in 81 patients with a total of 1,518 intravenous drug mixtures, 616 mixtures were known to be compatible, 61 mixtures were incompatible, while 841 mixtures no information.